Study of the potential for solar power plant at At Taqwa Mosque Using PV Syst - Sumarno, Radiktyo Nindyo; Muntasiroh, Laily; Mariani, Dina (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2024)
Countries located on the equator have a relatively high intensity of solar radiation. The thing that is most needed in a solar power plant is the intensity of solar radiation. Based on this, Indonesia is very suitable for implementing solar power plants. The power produced by a solar power plant is directly pro-portional to the intensity of solar radiation received by the solar panels. To maximize electrical power production, it is necessary to design a series of solar panel units to be connected in series or parallel. Solar panels connected in parallel will increase the nominal total voltage, whereas when connected in series they will increase the nominal total current. This research discusses the effect of the series-parallel configuration of solar panel installation on the power production received in a building in the campus environment. The method used to obtain the most optimal energy production is to use a combination of series and parallel solar panels. Daily sunlight data is simulated via PvSyst. The research results show that the most optimal energy production is obtained by designing a series circuit of 20 panels combined with a parallel circuit of 5 panels. The more modules connected in series, the total voltage will increase. The more modules that are connected in parallel, the total current will increase.